Algunos metabolitos presentes en el mixomicete Physarella oblonga (2010)
ABSTRACT: Myxomycetes are very attractive microorganisms to search biologically active compounds, because their ecological characteristics allowing them to be challenging with other organisms such as fungi, bacteria and parasites. This study was carried out to allalyze the production of several secondary metabolites from Physarella oblonga, and establish their presence by NMR spectroscopy; so, polyunsaturated fatty acids and stigmasterol were isolated and identified. The tirst one are typical of myxomicetes, but the latter is reported only in sorne species of the order Physarales.